“A gente já cresceu muito”: dos des/encontros da formação docente inclusiva aos indícios de desenvolvimento profissional no ensino de inglês para idosos - Silveira, Karyne Soares Duarte (2020)
Initial teacher education socially committed to inclusive education requires all teachers involved to mobilize knowledge about their work context, their students as well as a broader understanding about their own practice. Therefore, this qualitative interpretative research aims at analyzing the effects of English teaching to elderly citizens in two novice teachers’ practice, at the Universidade Aberta à Maturidade (UAMA). The following specific objectives were established: (i) to identify the representations of teachers’ work at UAMA mentioned by the teachers in their empirical texts; (ii) to investigate the representations revealed about the dimensions of teachers’ work at UAMA; and (iii) to analyze how teachers’ practice is reframed by the teachers in the context of English teaching to elderly students. In order to reach these goals, in line with the contemporary Applied Linguistics paradigm, engaged with an ethical agenda involving research, action and intervention in social life (CELANI, 2005; MOITA LOPES, 2006), the theoretical framework for this research was based in two main discussions: firstly, the perspective of teacher education devoted to transforming the social reality (ZEICHNER, 2008; FONTOURA, 2017), focused on inclusive education and its interface with foreign language teaching (MEDRADO; CELANI, 2017a; FONTANA, 2017), and taking into account English teaching to elderly students (MACHADO; CHAVES; OLIVEIRA, 2009; PORTO, 2018); secondly, the investigation on teachers’ work, in terms of professional development, and how to reframe teachers’ practice in light of Sociodiscursive Interactionism (BRONCKART, 2006, 2008, 2012; MACHADO, 2004; MACHADO; BRONCKART, 2009), related to the Labor Sciences (AMIGUES, 2004; SAUJAT, 2004; CLOT, 2007, 2010a, 2010b). The analytical categories adopted were defined according to the organizational, enunciative and semantic levels of the texts. Two teachers in initial education in the Letters-English undergraduate program at the Universidade Estadual da Paraíba (UEPB) were the collaborators of this research; they taught together the English course to the elderly students at UAMA through the extracurricular project entitled “Let’s speak English: experiência de ensino-aprendizagem de língua inglesa para idosos”, under the supervision of this researcher. The corpus consists of transcriptions of simple self-confrontation interviews (CLOT, 2007) carried out with the collaborators, and results revealed, as most relevant themes in their texts, evaluations related to: (i) encounters of the work collective; (ii) encounters with the elderly students; and (iii) the impact of these encounters in teachers’ work. Based on the linguisticdiscursive analysis of the above-mentioned themes, nuances of prescribed and realized work were identified, as well as a less visible dimension, the real work, emphasizing the emotions and the ways teachers (re)construct meanings about their pedagogical practice regarding the conflicts provided by the encounters. The results and discussion carried out signal how inclusive contexts may affect teachers’ work in initial education, unveiling evidence of professional development.